2009
DOI: 10.1080/07357900802427927
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Inhibits Colon Cancer Cell GrowthIn Vitroand Tumor GrowthIn Vivovia Induction of Apoptosis

Abstract: The present study was to investigate the anticancer effect of chloroquine on proliferation of mouse colon cancer cell line CT26 in vivo and in vitro and the possible mechanism. We found that chloroquine inhibited CT26 proliferation by concentration- and time-dependent manner. This effect was associated with apoptosis induction and decreased level of phosphorylated p42/44 mitogen-activated protein kinase and phosphorylated Akt. The in vivo study showed chloroquine-reduced tumor volume and prolonged survival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 35 publications
9
51
1
2
Order By: Relevance
“…In addition, we observed a significant decrease of tumor growth in mice treated with the autophagy inhibitor HCQ, used at a concentration that had no effect on cell proliferation (data not shown). These observations are in agreement with recent reports indicating that inhibition of autophagy by HCQ inhibits in vitro cell growth and in vivo tumor growth via induction of apoptosis (37,38). Our results are also supported by several studies showing that inhibition of autophagy promotes cancer cell death (39) and potentiates anticancer treatments (19,40,41).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we observed a significant decrease of tumor growth in mice treated with the autophagy inhibitor HCQ, used at a concentration that had no effect on cell proliferation (data not shown). These observations are in agreement with recent reports indicating that inhibition of autophagy by HCQ inhibits in vitro cell growth and in vivo tumor growth via induction of apoptosis (37,38). Our results are also supported by several studies showing that inhibition of autophagy promotes cancer cell death (39) and potentiates anticancer treatments (19,40,41).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported activity with these agents in other cell lines, and in many instances an apoptotic response was induced. 47,48 Chloroquine has been reported to induce apoptosis due to lysosomal disruption, mitochondrial membrane permeabilization and decreased protein degradation. 20,49 Others have reported both apoptosis and necrosis which is concentration dependent, 50 or indeed involvement of apoptosis-independent death.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…While there was a substantial difference in tumor size, it is important to note that 3PO treatment alone did not have the same anti-tumor effects that were seen in the previously published work [53], although the tumor model (Lewis lung carcinoma tumors in C57/BL6 mice) was the same. Additionally, although the model system was different, tumors from animals treated with chloroquine alone failed to show any difference in tumor size, contrasting with other published tumor studies [183,184]. While this may be due to the use of slower growing tumor models that are not as sensitive to chloroquine the LLC tumors grew very quickly, with the first tumors palpable merely three days after inoculation.…”
Section: Pharmacologic Inhibition Of Autophagy In Combination With 3pcontrasting
confidence: 51%
“…Based on previously reported animal tumor studies using chloroquine, a dose of 50mg/kg was selected [36,54,183,184]. The dose of 3PO used for this study (0.07mg/g) was also selected based on a previously published animal tumor model [53].…”
Section: Pharmacologic Inhibition Of Autophagy In Combination With 3pmentioning
confidence: 99%